2021
DOI: 10.1155/2021/6615001
|View full text |Cite
|
Sign up to set email alerts
|

Association of Polymorphisms in Vitamin D-Metabolizing Enzymes DHCR7 and CYP2R1 with Cancer Susceptibility: A Systematic Review and Meta-Analysis

Abstract: The deficiency of vitamin D has been reported to be relevant to cancer risk. DHCR7 and CYP2R1 are crucial components of vitamin D-metabolizing enzymes. Thus, accumulating researchers are concerned with the correlation between polymorphisms of DHCR7 and CYP2R1 genes and cancer susceptibility. Nevertheless, the conclusions of literatures are inconsistent. We conducted an integrated review for the correlation of DHCR7 and CYP2R1 SNPs with cancer susceptibility. In the meanwhile, a meta-analysis was performed usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
31
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(31 citation statements)
references
References 40 publications
0
31
0
Order By: Relevance
“…What’s more, we had some novel discoveries of the hub mRNAs in exosomes, such as CYP2R1 and BTLA, that haven’t been reported in exosomes but have important functions. CYP2R1 are crucial components of vitamin D-metabolizing enzymes ( 32 ). Recent results suggested that high vitamin D concentration was associated with a lower odds ratio of GC in Korean adults ( 33 ).…”
Section: Discussionmentioning
confidence: 99%
“…What’s more, we had some novel discoveries of the hub mRNAs in exosomes, such as CYP2R1 and BTLA, that haven’t been reported in exosomes but have important functions. CYP2R1 are crucial components of vitamin D-metabolizing enzymes ( 32 ). Recent results suggested that high vitamin D concentration was associated with a lower odds ratio of GC in Korean adults ( 33 ).…”
Section: Discussionmentioning
confidence: 99%
“…At the same time, 7-DHC is a key substrate for the production of vitamin D3 19 . In recent years, increasing publications have put forth a functional link between DHCR7 and a diverse variety of tumors 5,20 . However, the speci c mechanism or underlying pathway by which DHCR7 promotes the tumorigenesis and tumor progression remains poorly understood.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, DHCR7 is considered as a key focus for current tumor research. Although there is clear evidence of that DHCR7 polymorphisms are associated with an increased risk of various tumors, the causal relationship between its abnormal expression with tumorigenesis is still unclear, and its effect on the development of different kinds of tumors and its molecular mechanism are still controversial [5][6][7] .…”
Section: Introductionmentioning
confidence: 99%
“…Unfortunately, no other studies have yet searched for the role of this gene in thyroid gland neoplasms. DHCR7 is one of a few genes found to influence 25(OH)D plasma level in GWAS [ 69 ]. Rs12785878 SNP was also found to increase a general cancer risk in a meta-analysis of five studies including patients with breast, hepatocellular, and thyroid cancer [ 69 ].…”
Section: Discussionmentioning
confidence: 99%